2016
DOI: 10.21633/jgpha.6.2s14
|View full text |Cite
|
Sign up to set email alerts
|

Engaging homeless service providers in educational efforts during a tuberculosis outbreak in Atlanta

Abstract: Background: During an outbreak of tuberculosis (TB) in the homeless population of metropolitan Atlanta, education of homeless service providers (HSPs) about the implementation of local infection control measures was imperative to limiting the spread of TB and to preventing future outbreaks.Methods: By use of educational sessions and teaching posters, two interventions were designed to focus educational efforts from November 2014 to August 2015: 1) a spatially-targeted approach that identified HSPs within an ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Finally, the service providers in our study averaged only 2.4 years of experience at the transitional housing site. Yet, it must be noted that burnout is high among workers in this field; in fact, a Canadian study found that half of workers in the homeless sector had been employed there for less than 2 years (Schiff & Lane, ); problems with high staff turnover among homeless sector service providers have also been noted in the United States (e.g., Nandi et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the service providers in our study averaged only 2.4 years of experience at the transitional housing site. Yet, it must be noted that burnout is high among workers in this field; in fact, a Canadian study found that half of workers in the homeless sector had been employed there for less than 2 years (Schiff & Lane, ); problems with high staff turnover among homeless sector service providers have also been noted in the United States (e.g., Nandi et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The Fulton County Board of Health and Mercy Care, a local federally qualified health center, formed the Metro Atlanta TB Task Force in June 2014 with various stakeholders, including the Fulton County Department of Health and Wellness, the Centers for Disease Control and Prevention, Emory University, and shelter directors. 23,24 The Task Force modeled guidelines after programs in San Francisco and Los Angeles to enforce a standardized TB screening policy for shelter residents, implement administrative controls designed to identify possible cases and reduce the spread of TB, design educational campaigns to inform PEH of the ongoing outbreak and encourage TB screening, and describe general infection control practices to be used by shelter staff members (Table 1). 25 The TB Task Force generated and disseminated preliminary guidelines to shelters and public health workers in November 2014; however, by December 2014, it was clear that immediate active dissemination and implementation of the guidelines had not occurred.…”
Section: Program Descriptionmentioning
confidence: 99%
“…23,25 In January 2015, to implement guidelines more quickly, additional educational initiatives (eg, information sessions, distributing teaching posters) were conducted by public health workers at shelters to support citywide implementation of guidelines. [23][24][25] The standardized TB screening policy that was enforced required all PEH seeking to enter a shelter to undergo a TB symptom screen (Box) and provide documentation, within 7 days of arrival at a facility, of a negative TB test result (tuberculin skin test or interferon gamma release assay) in the past 6 months or documentation that they were actively undergoing treatment for latent TB infection. 21,[23][24][25] PEH with a positive TB test result were required to undergo further evaluation.…”
Section: Program Descriptionmentioning
confidence: 99%
“…In addition, the guidelines included the following principles: appointment of a TB liaison at each of the 6 shelters, isolation or separation of residents with cough, maintenance of a bed log that includes every resident’s name and sleeping location within the facility, provision of a TB clearance card at the time each person completed screening to allow them access to the 6 shelters, and random inspections of the shelters by the health department to ensure adherence to the guidelines and to provide ongoing staff education. Because publication of the guidelines did not lead to their immediate uptake at all 6 shelters, educational initiatives were undertaken to increase TB knowledge and awareness of guideline content among shelter staff and the homeless community ( 3 ). …”
Section: The Studymentioning
confidence: 99%